IMPLEMENTASI PEMBELAJARAN OPEN ENDED BERBASIS APOS - Andri Suryana; Mirna Herawati; Fadjriyah Hapsari (Community : Jurnal Pengabdian Pada Masyarakat, 2021)
Teachers as educators are expected to continuously improve their professional abilities, especially in the field of teaching, including elementary school teachers. However, there are still elementary school teachers who use conventional learning in delivering learning materials to students. As a result, students are less able to develop their cognitive, affective, and psychomotor abilities. One of the lessons that can overcome this is the APOS-based Open ended. Open-Ended is a type of learning in which the teacher provides a problem situation to students whose solutions or answers to these problems can be obtained in various ways. To implement this learning, learning stages are needed. In this case, the Open-Ended learning stage is based on APOS. APOS is a constructivist theory about how students construct concepts through 4 things, namely Actions, Processes, Objects, and Schema. These 4 things are done through the ACE cycle, namely activities, class discussions, and practice questions (Exercises). The results of this community service activity are that it turns out that this activity is able to provide alternative solutions to develop the abilities and dispositions of students at the elementary level through the implementation of APOS-based open ended learning.